Sign Language Acquisition - and Meier, Richard P. (Oxford Handbook Topics in Linguistics, 2016)
This essay considers the acquisition of sign languages as first languages. Most deaf children are born to hearing parents, but a minority have deaf parents. Deaf children of deaf parents receive early access to a conventional sign language. The time course of acquisition in these children is compared to the developmental milestones in children learning spoken languages. The two language modalities—the oral-aural modality of speech and the visual-gestural modality of sign—place differing constraints on languages and offer differing resources to languages. Possible modality effects on first-language acquisition are considered. Historically, many deaf infants born to hearing parents have had little access to a conventional language. However, these children sometimes elaborate “home sign” systems. Lastly, the role of early experience in language acquisition is considered. Deaf children of hearing parents are immersed in a first language at varying ages, enabling a test of the critical-period hypothesis.
Keywords: Björn-2026-02-22